Hubungan Pola Makan Pasien CKD dengan Indeks Massa Tubuh (IMT) Pasien yang Menjalani Hemodialisa di RS Dik Pusdikkes Kodiklat AD: The Relationship Between the Dietary Patterns of CKD Patients and the Body Mass Index (BMI) of Patients Undergoing Hemodialysis at the Dik Pusdikkes Kodiklat AD Hospital - Devi Sukanti; Bambang Suryadi; Sumedi (MPI Press, 2021)
Introduction: Dietary factors or eating patterns can cause patients to experience anorexia so that it affects the body mass index measured by CKD patients (Susetyowati, 2014). Therefore, it is important to understand the research when studying the relationship between the diet of CKD patients and the body mass index of patients undergoing hemodialysis at the Dik Pusdikkes Hospital in 2021. Objective: This study aims to determine how big the influence of the relationship between the diet of CKD patients and the body mass index of patients undergoing hemodialysis to improve the quality of life of CKD patients. Method: The type of research used is quantitative research with a correlational design to determine whether there is a relationship between variables using experimental research. The population in this study that became the study population were all hemodialysis patients at the AD Pusdikkes Hospital. The sampling technique used was total sampling. The research instrument used is a questionnaire. The questionnaire is not standardized so that validity and reliability tests are carried out. In this study, the analysis used the chi-square test. Results: the results of the chi-square test showed that the p-value (0.028) <0.05 then Ha was accepted or there was a relationship between the diet of CKD patients and the patient's body mass index. Conclusion: Based on the results of the analysis of the relationship between the evaluation of hemodialysis patients at RS Dik Pusdikkes Kodiklat AD, 9 respondents had a poor diet with a body mass index in the lean category of 6 people (66.7%) and the normal category of 3 people (33.3%). And 11 respondents have a good diet relationship with body mass index in the thin category of 2 people (40.0%) and the normal category of 12 people (60%).